C(sp)-C(sp) Lever-Based Targets of Orientational Chirality: Design and Asymmetric Synthesis - Ting Xu; Jia-Yin Wang; Yu Wang; Shengzhou Jin; Yao Tang; Sai Zhang; Qingkai Yuan; Hao Liu; Wenxin Yan; Yinchun Jiao; Xiao-Liang Yang; Guigen Li (Molecules, 2024)
In this study, the design and asymmetric synthesis of a series of chiral targets of orientational chirality were conducted by taking advantage of N-sulfinylimine-assisted nucleophilic addition and modified Sonogashira catalytic coupling systems. Orientational isomers were controlled completely using alkynyl/alkynyl levers [C(sp)-C(sp) axis] with absolute configuration assignment determined by X-ray structural analysis. The key structural element of the resulting orientational chirality is uniquely characterized by remote through-space blocking. Forty examples of multi-step synthesis were performed, with modest to good yields and excellent orientational selectivity. Several chiral orientational amino targets are attached with scaffolds of natural and medicinal products, showing potential pharmaceutical and medical applications in the future.